Strategies and interlanguage pragmatics: Explicit and comprehensive - Sykes, Julie M.; Cohen, Andrew D. (Studies in Second Language Learning and Teaching, 2018)
Explicit instruction in strategies for interlanguage pragmatic learning is fundamental to the development of a comprehensive set of pragmatic abilities in the target language. In this article, we begin by providing an overview of previous work in the area of language learner strategies directed at the teaching and learning of pragmatics. We then offer an extension of Cohen’s (2005, 2014) framework of strategies for learning, using, and evaluating the use of interlanguage pragmatics in four domains: knowledge, analysis, subjectivity, and awareness (Sykes, Malone, Forrest, & Sadgic, forthcoming). Examples from current projects are provided to exemplify the critical importance of a strategies-based approach to the teaching and learning of interlanguage pragmatics. The article concludes with ideas for future research and implementation.